MENGULIK SEJARAH MUSEUM WASAKA DAN KONTRIBUSINYA BAGI KOTA BANJARMASIN - Suryadi, Suryadi; Dewi, Priska Fitria; Sunarno, Ali; Desy, Lili; Dayana, Etnisa; Cristia, Veronicha Rut (Universitas Negeri Gorontalo, 2024)
The Wasaka Museum in Banjarmasin plays a pivotal role in enhancing historical awareness and knowledge of local culture. This research, employing historical and qualitative methods, gathered data through interviews, observations, and documentation to analyze the museum's contribution to the city's development. With collections including traditional weapons, ceremonial attire, paintings, and significant documents, the museum not only preserves artifacts but also serves as a cultural learning center. It aids in uncovering hidden cultural values and promotes the history and cultural beauty of Banjarmasin, significantly contributing to the formation of Indonesian society and urban development, with a vision to become a center for the preservation of historical values.